Coronavirus Anxiety and Obsession and Their Relationship With Depression and Activities of Daily Living in Older Adults - Vahid Rashedi; Mostafa Roshanravan; Vahidreza Borhaninejad; Marzieh Mohamadzadeh (University of Social Welfare & Rehabilitation Sciences, 2022)
Objectives In addition to physical damage, the coronavirus disease 2019 (COVID-19) can cause psychological problems in people. The present study aims to assess the prevalence of anxiety and obsession caused by the COVID-19 in the elderly and their relationship with depression and the ability to perform activities of daily living (ADL). Methods & Materials This descriptive-analytical study with a cross-sectional design was conducted on 300 older adults aged ≥60 years in Maneh and Samalghan county who were selected by a simple random sampling method. Data were collected by using a demographic form, the coronavirus anxiety scale (CAS), obsession with COVID-19 scale (OCS), ADL scale, Instrumental ADL scale, and geriatric depression scale (GDS). Data analysis was performed in SPSS v. 18 using Mann-Whitney U, Kruskal-Wallis, and Spearman's correlation tests. Results Among participants, 214 (71.2%) had age <70 years. The prevalence of OCS and CAS in the elderly was 5.3% and 9%, respectively. Statistical analysis showed that the scores of OCD (r=0.220, P<0.001) and CAS (r=0.322, P<0.001) had a significant correlation with depression. The CAS score had a significant negative correlation with ADL (r=-0.114, P<0.05) Conclusion The prevalence of obsession and anxiety caused by the COVID-19 in the elderly is not different from that in other age groups. However, there is significant increase in them during the COVID-19 pandemic compared to their pre-pandemic levels. it seems necessary to pay attention to screening, referral, and more detailed follow-up of mental health services in clinics and health centers for the elderly during the COVID-19 pandemic.